(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article analyzes the effective methods of using digital technologies in the field of tourism. Also, the author’s approaches and proposals for the use of digital technologies in the field of tourism are presented.